2004
DOI: 10.1177/0011000003261356
|View full text |Cite
|
Sign up to set email alerts
|

A Reaction to Counseling Psychology and School Counseling

Abstract: Counseling psychologists and school counselors share some similarities in their history, training, and experiences. Although these similarities have fostered a common interest in educational and developmental interventions among children and some shared theoretical language, there remains several hurdles to effectively collaborating created by the significant differences in these two professions. Romano and Kachgal (2004 [this issue]) present readers with a poignant historical and evolutionary perspective of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Yet the interest and resolve of counseling psychologists in helping K-12 youth within the school environment have been questioned (Lichtenberg & Goodyear, 2004;Pope, 2004). Those who advocate for a more active role for counseling psychologists in schools specifically suggest more collaboration with school professionals (Forrest, 2004) and more help to show evidence for which interventions in schools are efficacious (Gysbers, 2004;Romano & Kachgal, 2004;Sabella, 2004;Whiston, 2004). Currently, resources for multiculturally competent counseling and psychotherapy (herein referred to as counseling) to comprehensively address the mental health needs of K-12 youth in schools are critically under funded (Coleman, 2004).…”
mentioning
confidence: 99%
“…Yet the interest and resolve of counseling psychologists in helping K-12 youth within the school environment have been questioned (Lichtenberg & Goodyear, 2004;Pope, 2004). Those who advocate for a more active role for counseling psychologists in schools specifically suggest more collaboration with school professionals (Forrest, 2004) and more help to show evidence for which interventions in schools are efficacious (Gysbers, 2004;Romano & Kachgal, 2004;Sabella, 2004;Whiston, 2004). Currently, resources for multiculturally competent counseling and psychotherapy (herein referred to as counseling) to comprehensively address the mental health needs of K-12 youth in schools are critically under funded (Coleman, 2004).…”
mentioning
confidence: 99%
“…[ 27 34 35 ] Some studies indicated the effectiveness of counseling services for the students. [ 36 37 ]…”
Section: Discussionmentioning
confidence: 99%
“…Providing direct service (e.g., facilitating specialized mental health groups), designing programs (e.g., teacher-teacher mentor program) and program evaluation (e.g., investigating effects of anti-bullying program) have been suggested as areas counseling psychologists could use their expertise to help K-12 schools (Gysbers, 2004;. Other scholars suggest counseling psychologists might supervise school counselors and conduct research on counseling outcomes in schools (Romano & Kachgal, 2004;Sabella, 2004). Recognizing counseling psychology's leadership regarding multicultural issues, Whiston (2004) believes, "Counseling psychologists could have a significant impact on youth from various backgrounds by providing training, resources, and materials on multiculturalism to school counselors" (p. 273).…”
Section: Moving Forwardmentioning
confidence: 99%